The Usborne book of dinosaurs - Mayes, Susan; Rey, Luis; Trotter, Stuart ([Tulsa, Okla. : EDC], 2004)
An illustrated introduction to the basic types of dinosaurs.
"First published in America 1993"--Colophon.
Includes index.
4.5
K-3
Keywords: Dinosaurs -- Juvenile literature; Dinosaurs; Dinosaurs